The volatility of nuclear politics in the Middle East - Khan, Jesmeen (2016)
Israel’s recent aerial military exercise provoked speculation of Israeli plans to attack Iran’s nuclear facilities. The repercussions of such an attack would reverberate beyond the Middle East.